PEDAGOGICAL PRINCIPLES OF SPEECH DEVELOPMENT OF STUDENTS OF PRIMARY CLASS AGE (Academia Science Repository, 2023)
The article reveals the theoretical foundations for creating school projects and considers the practical aspects of preparing bachelors and masters of a pedagogical university for organizing project activities in elementary school. The differences between the school project and the reproducible pedagogical process, the stages of the implementation of project activities are highlighted, and a contradiction is identified, proving the need to prepare future elementary school teachers for the organization of project activities.